Contraceptive method preference and use among married woman garment workers (Journal of Dhaka National Medical College & Hospital, 2016)
Objective: To assess the contraceptive method preference and use among married woman garment workers.Method and materials: A cross sectional descriptive study was carried out among 171 married woman garment workers of 15 - 49 years old in Dhaka city in a 6 months period from January 2012 to June 2012.Result: Among the respondent, majority (53%) were between the age group of 26 to 31 years and belonged to low socio economic group. Most of the respondent (80%) living in nuclear families. In both the aspect of husband and wives, very few (around 30%) had primary level or more of education. Out of the 171 respondents, mean age of first marriage was 18 years. About the use of contraception, 64% were using oral pills, 23% were using injection, 8% were using condoms and 5% used copper-T. Majority (63%) of the respondent starting using contraceptive within one month of the marriage and took decision about the contraceptive jointly both by husband and wife. It is found that 70% of the respondent collected contraception from the health complex. Pregnancy status among the respondent (8%) were pregnant at the time of study. Among the respondent 12% become mother before their first anniversary due to lack of knowledge regarding contraceptive methods and use and also husband's opposition was stated as the non-use of contraceptive methods. The main form of complaints of pill-users were vertigo and nauseaConclusion: Current contraceptive use rate was 75% and 25% of women were non-users Moderate use rate may be attributed to several socio-economic and cultural factors such as education, limited excursion, facilities, husband-wife communication, occupation and economic condition and also 8% of them were pregnant at the time of study was on-going. In addition women face difficulties in obtaining contraceptive supplies and lack of knowledge of contraceptive method.J. Dhaka National Med. Coll. Hos. 2016; 22 (02): 25-27